Morfología y biometría de cinco poblaciones de Artemia franciscana (Anostraca: Artemiidae) - Correa Sandoval, Francisco (Universidad de Costa Rica, 1993)
The morphometric characteristics of two Artemá populations from Baja California, Mexico, were compared 10 those of three A. franciscana populations from the Artemía Referenee Center, Belgium, (San Francisco Bay, U.S.A.), San Francisco Bay Brand, U.S.A., and Yavaros, México. The general morphology was similar but we found significant differenees in all biometric features analyzed; although, the Baja Californian populations belong 10 the same species. These populations have acquired some features of their own, which probably are environment-dependent and genetically fixed. This might be sufficient 10 define them as microgeographic varieties of A.franciscana